Isotretinoin – Induced AGEP: A Case Report - Alotaibi HM; AlNasser S; Aldossari A; Alluhaybi A; Alsergani R; Alrajban W (International Medical Case Reports Journal)
Hend M Alotaibi,1 Sultan AlNasser,1 Abdulelah Aldossari,2 Abdulrahman Alluhaybi,1 Reem Alsergani,1 Waleed Alrajban1 1Department of Dermatology, College of Medicine, King Saud University and King Saud University Medical City (KSUMC), Riyadh, Saudi Arabia; 2Department of Dermatology, King Fahad Specialist Hospital, Buraydah, Saudi ArabiaCorrespondence: Sultan AlNasser, Email SultanAlNasser70@gmail.comAbstract: Acute Generalized Exanthematous Pustulosis (AGEP) is a relatively rare but severe dermatological adverse reaction characterized by the rapid onset of generalized erythema, coupled with numerous sterile nonfollicular pustules. Agents commonly implicated in triggering AGEP include antibiotics, antifungals, antimalarials, and diltiazem. We present a case of a isotretinoin induced AGEP in a young female patient known to have guttate psoriasis, inverse and scalp psoriasis. She was started on Isotretinoin as she had inflammatory acne as well. Three days later, she developed pruritic, erythematous lesions, some vesicles with a yellowish exudate over the armpits, upper chest, upper arms, and legs. A skin biopsy was performed, which, in conjunction with the clinical presentation, was suggestive of AGEP. In 2010, Filho et al described the first case of isotretinoin-induced AGEP in a female patient diagnosed with Hidradenitis Suppurativa. The EuroSCAR tool was utilized to assess the lesion morphology, clinical course, and histological outcomes, which validated the diagnosis. Using the same criteria, our patient was categorized as “definite AGEP”, further supporting the isotretinoin-induced AGEP hypothesis. This report highlights isotretinoin as a possible trigger for AGEP, emphasizing the crucial role of a thorough history and vigilant clinical assessment in early identification and management of such reactions.Keywords: acute generalized exanthematous pustulosis, isotretinoin, pustular psoriasis, drug reactions